2016
DOI: 10.1038/srep20438
|View full text |Cite
|
Sign up to set email alerts
|

Knockin of Cre Gene at Ins2 Locus Reveals No Cre Activity in Mouse Hypothalamic Neurons

Abstract: The recombination efficiency and cell specificity of Cre driver lines are critical for exploring pancreatic β cell biology with the Cre/LoxP approach. Some commonly used Cre lines are based on the short Ins2 promoter fragment and show recombination activity in hypothalamic neurons; however, whether this stems from endogenous Ins2 promoter activity remains controversial. In this study, we generated Ins2-Cre knockin mice with a targeted insertion of IRES-Cre at the Ins2 locus and demonstrated with a cell lineage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 42 publications
0
18
0
Order By: Relevance
“…To our knowledge, this is the first report of insulin production in ChP. Previous work with insulin reporter genetic models demonstrated Ins2 expression in murine ChP (38,39) but no Ins2 promoter activity in any other brain structure. These models, however, failed to detect insulin mRNA or its corresponding protein.…”
Section: Discussionmentioning
confidence: 61%
“…To our knowledge, this is the first report of insulin production in ChP. Previous work with insulin reporter genetic models demonstrated Ins2 expression in murine ChP (38,39) but no Ins2 promoter activity in any other brain structure. These models, however, failed to detect insulin mRNA or its corresponding protein.…”
Section: Discussionmentioning
confidence: 61%
“…To generate b-cell-specific knockout (bKO) mice of Tph1, Htr2b, Prlr, and Stat5, Ins2-Cre (MGI 2387657) mice were mated with mice harboring a Tph1 floxed allele (MGI 6271993), an Htr2b floxed allele (MGI 3837400), a Prlr floxed allele, and a Stat5 floxed allele (MGI 3055318), respectively (9)(10)(11)(12)(13)(14). To generate Ghr bKO mice, Ins2-Cre mice were mated with mice harboring a Ghr floxed allele (MGI 5056123) (15,16). All Cre mice used in this study lacked the GH minigene, which has been shown to induce ectopic 5-HT production (17,18).…”
Section: Animal Experimentsmentioning
confidence: 99%
“…3l, n = 10). Since Rip-Cre has been previously implicated in hypothalamus and hippocampus 17 . As shown in supplementary Fig.…”
mentioning
confidence: 99%